Design of feedforward compensator for temperature control system in electric water heater - Wongkinee, Kobdate; Bomsuwan, Bunchar; Lenwari, Wanchak (Asia-Pacific Journal of Science and Technology, 2017)
This paper proposes the design and principle to enhance the performance of the temperature control system in an electric water heater which rapidly controls a temperature of water outlet under disturbances i.e. a condition of an unsteady fl ow inlet. The ability of a proposed control system employing PID plus Feedforward is investigated in particular the immunity to disturbances which is the main aim of this research. Microcontrollerbased control system is used to generate signals and control power delivered to the heater. The design procedure of proposed method is presented. The experimental results confi rm the excellent control response in particular to disturbances and effectiveness of this improved temperature control system. The proposed system can be applied to develop the electric water heater to be an energy effi cient appliance in the future.